The Art of Theoretical Biology - Matthäus, Franziska 1975-; Matthäus, Sebastian; Harris, Sarah; Hillen, Thomas 1966- (Springer, 2020)
This beautifully crafted book collects images, which were created during the process of research in all fields of theoretical biology. Data analysis, numerical treatment of a model, or simulation results yield stunning images, which represent pieces of art just by themselves. The approach of the book is to present for each piece of visualization a lucid synopsis of the scientific background as well as an outline of the artistic vision